SUCCESFUL MANAGEMENT OF DYSTOCIA DUE TO PEROSOMUS ELUMBIS IN A HOLSTEIN FRIESIAN COW – A CASE REPORT - J, ARUNPANDIAN; J, DENY; N, SRIVASTAVA; S, GOVINDHASAMY; SIVAN G, ASWINI (The Indian Journal of Animal Reproduction, 2023)
A five-year-old female cow was presented to the Dharmapuri district veterinary clinic, Tamil Nādu with severe straining and ruptured first water bag. Per vaginal examination revealed incompletely dilated cervix, and foetal parts were not palpable. The treatment included induction therapy for further dilatation of cervix. The abnormality of the foetal parts may lead to certain congenital anomaly. After thorough lubrication of the birth canal mild traction was applied to deliver the impacted fetus. The morphological appearance of the stillborn calf revealed that the condition was perosomus elumbis. The cow had an uneventful recovery.